2018
DOI: 10.1111/scd.12291
|View full text |Cite
|
Sign up to set email alerts
|

Anterior tooth wear and quality of life in a nursing home population

Abstract: Results suggest that tooth wear is negatively related to quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Furthermore, in a study conducted by Barlett et al [ 10 ] on TW, they concluded that erosion was directly associated with age and gender showed no association with erosive wear. As per a study conducted by Allaq et al [ 11 ] regarding TW in a population, TW is directly linked to the age of that population, which is also in line with our study’s inference. In addition, factors, such as changes in saliva composition and oral health conditions, which become more common with age, can contribute to TW.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in a study conducted by Barlett et al [ 10 ] on TW, they concluded that erosion was directly associated with age and gender showed no association with erosive wear. As per a study conducted by Allaq et al [ 11 ] regarding TW in a population, TW is directly linked to the age of that population, which is also in line with our study’s inference. In addition, factors, such as changes in saliva composition and oral health conditions, which become more common with age, can contribute to TW.…”
Section: Discussionsupporting
confidence: 93%
“…A series of studies designated anterior tooth wear as esthetically unpleasant [16][17][18]. Furthermore, anterior tooth wear negatively affected the quality of life in elder nursing home patients [19].…”
Section: Introductionmentioning
confidence: 99%